Plasma interleukin-27 levels in patients with coronary artery disease. Issue 43 (October 2017) - Miura, Kotaro; Saita, Emi; Suzuki-Sugihara, Norie; Miyata, Koutaro; Ikemura, Nobuhiro; Ohmori, Reiko; Ikegami, Yukinori; Kishimoto, Yoshimi; Kondo, Kazuo; Momiyama, Yukihiko
Abstract : Abstract: Interleukin (IL)-27, one of cytokines in the IL-12 family, is considered to have both pro- and anti-inflammatory properties. However, blood IL-27 levels in coronary artery disease (CAD) have not been fully elucidated yet. This cross-sectional study was done to elucidate the association between blood IL-27 levels and CAD. We investigated plasma IL-27 and high-sensitivity C-reactive protein (hsCRP) levels in 274 consecutive patients who underwent elective coronary angiography for suspected CAD. CAD was present in 177 patients [30 acute coronary syndrome (ACS) and 147 stable CAD]. Compared with 97 patients without CAD, 177 patients with CAD had higher IL-27 (median 0.26 vs 0.22 ng/mL, P < .05) and higher hsCRP (0.98 vs 0.41 mg/L, P < .001) levels. However, there was no significant difference in IL-27 levels among 3 groups of ACS, stable CAD, and CAD(-) (0.26, 0.25, and 0.22 ng/mL), whereas hsCRP levels were significantly higher in ACS and stable CAD than in CAD(-) (2.09, 0.91 vs 0.41 mg/L, P < .001) and were highest in ACS. IL-27 levels tended to increase with the number of >50% stenotic coronary vessels: 0.22 in CAD(-), 0.22 in 1-vessel disease, 0.31 in 2-vessel disease, and 0.27 ng/mL in 3-vessel disease ( P < .05). A stepwise increase in hsCRP levels was also found: 0.41 in CAD(-), 0.75 in 1-vessel, 1.05 in 2-vessel, and 1.85 mg/L in 3-vessel disease ( P < .001). Plasma hsCRP levels significantly ( r = 0.35), but IL-27 levels weakly ( r = 0.15), correlated with the number of stenotic coronary segments. In multivariate analysis, both IL-27 and hsCRP levels were independent factors associated with CAD. However, hsCRP, but not IL-27, was also a factor for ACS. While plasma IL-27 levels were high in patients with CAD, these levels were an independent factor for only CAD, not ACS, and weakly correlated with the severity of CAD. Our results suggest that IL-27 is unlikely to be a good biomarker reflecting the severity of CAD or the presence of ACS, or to play a major role in the progression of CAD.